Πάτερ ἡμῶν (Our Father) in Matthew 6:9: Reconstructing and negotiating a Christian identity in the 1st century CE - M’bwangi, Fednand M. (HTS teologiese studies, 2022)
To the question of why Matthew includes the phrase Πάτερ ἡμῶν (Our Father) in his version of the Lord’s Prayer, scholars guided by different theories answer this question differently. Employing literary criticism ranging from form, source and tradition history to reader–audience response and socio-rhetorical interpretation, scholars contend that Matthew composed the concept Πάτερ ἡμῶν (Our Father) as a crucial segment of his version of the Lord’s Prayer, either to present an opposition between Father who dwells in heaven and the Earth, which is humanity’s dwelling place, or to evoke a community relationship to God in the context of welcoming God’s rule, or to present the Lord’s Prayer as God’s gift for creating order, community and transformation in society. In view of this inconsistent conception of the function of Matthew’s concept ‘Our Father’, the goal of this study is to employ semantic analysis and social identity theory (SIT) to analyse Matthew 6:9 to defend the argument that Matthew employed the concept Πάτερ ἡμῶν in the 1st century CE firstly to reconstruct the Christian identity of his community by identifying with the early Christian community and accommodating Jewish traditions and then to negotiate it by contesting the Roman Empire.Contribution: The interdisciplinary contribution of the study in tandem with the expectations of HTS Teologiese Studies/Theological Studies has been attained through the application of a collective SIT prism of identification, accommodation and contestation to read the social function of Matthew’s concept Πάτερ ἡμῶν in reconstructing and negotiating the identity of his community in 1st century Roman society.